Heterojunctions formed by annealing of GaSe and InSe layered crystals in zinc vapor - Kudrynskyi, Z. R.; Kovalyuk, Z. D. (Technology and design in electronic equipment, 2012)
The article presents a method of creating heterojunc¬tions based on semiconductors with different lattice types. Substrates manufactured from GaSe and InSe layered crystals were annealed in Zn vapor. This way, n-ZnSe–p-GaSe and n-ZnSe–p-InSe heterojunctions were obtained. The obtained heterojunctions are photo¬sensitive in near and infrared spectral regions. This method opens up greate possibilities of producing heterostructures with a desired sensitivity band.